2022
DOI: 10.1002/anie.202201750
|View full text |Cite
|
Sign up to set email alerts
|

S,O‐Ligand Promoted meta‐C−H Arylation of Anisole Derivatives via Palladium/Norbornene Catalysis

Abstract: Reversing the conventional site-selectivity of CÀ H activation processes provides new retrosynthetic disconnections to otherwise unreactive bonds. Here, we report a new catalytic system based on palladium/ norbornene and an S,O-ligand for the meta-CÀ H arylation of aryl ethers that significantly outperforms previously reported systems. We demonstrate the unique ability of this system to employ alkoxyarene substrates bearing electron donating and withdrawing substituents. Additionally, ortho-substituted aryl et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 94 publications
2
26
0
Order By: Relevance
“…In 2016 Buchy et al investigated the Shapiro reaction with the use of the deuterated isopropylidene endgroup. Firstly, the two-step modification yielded (prop-1-en-2-yl-d5)lithium (35) from trisylhydrazone 34 upon treatment with the n-butyllithium and TMEDA. Trisyl hydrazone 34 was synthesized from deuterated acetone (33) and trisyl hydrazine.…”
Section: Shapiro and Bamford-stevens Reactions -Achievements In Recen...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016 Buchy et al investigated the Shapiro reaction with the use of the deuterated isopropylidene endgroup. Firstly, the two-step modification yielded (prop-1-en-2-yl-d5)lithium (35) from trisylhydrazone 34 upon treatment with the n-butyllithium and TMEDA. Trisyl hydrazone 34 was synthesized from deuterated acetone (33) and trisyl hydrazine.…”
Section: Shapiro and Bamford-stevens Reactions -Achievements In Recen...mentioning
confidence: 99%
“…In the second step, the desired product was obtained in 27% yield after reaction with MeLi. 35 Xu et al presented the visible-light-inducted annulation of phosphoryl diazomethylarenes and pyridinium 1,4-zwitterionic thiolates leading to the dicarboxylate derivatives. The diazophosphinates and diazophosphonates were synthesized from tosyl hydrazones 105a-p which reacted with sodium carbonate to yield the final products 106a-p in rather moderate yields.…”
Section: Author(s)mentioning
confidence: 99%
“…Moreover, Pd(II)-initiated Catellani-type reactions were developed as a new advance by the groups of Bach, 13 Yu, 5a Dong, 14 Zhou, 15 Zhang, 16 and Fernańdez-Ibańẽz. 17 In addition, a series of structurally modified NBEs (smNBEs) have been designed to finely tune the Catellani reaction in terms of chemo-, regio-, and enantioselectivities, as witnessed by the works of the Yu, 5b Dong, 18 and Zhou 19 groups. More recently, our group reported that the Catellani-type reaction can proceed without the participation of NBE by the development of an unstrained hybrid cycloolefin ligand, which extended the concept of Pd/ NBE catalysis to more general Pd/olefin catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…18 A similar strategy was recently applied to Pd(II)-initiated mono meta-arylation of anisole derivatives by the Fernańdez-Ibańẽz group. 17 Despite these advances, the smNBE strategy for overcoming the orthoconstraint still suffered from some limitations, such as diminished catalytic activity and limited scope of the electrophile. 25 We noticed that, for another synthetically useful reaction category, the ortho-alkylative Catellani-type reaction, a general solution to ortho-constraint, remained elusive (Scheme 1d).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation